A phenotypical male with 46,XX karyotype: A rare case report (Journal of Association of Clinical Endocrinologist and Diabetologist of Bangladesh, 2025)
The 46,XX testicular disorder of sex development (46,XX testicular DSD) is a rare phenotype. This disorder usually presents with varying degrees of clinical features, ranging from ambiguous to normal male genitalia. The usual presentation in adults is infertility. Here, we describe the clinical, biochemical, and cytological findings of a 28-year-old male patient with sex-determining region Y (SRY)-positive 46,XX testicular DSD presented with bilateral gynecomastia, erectile dysfunction, loss of libido, and infertility. Biochemical analysis revealed hyper gonadotrophic hypogonadism, and semen analysis showed azoospermia. Chromosomal analysis revealed 46,XX karyotype. Polymerase Chain Reaction (PCR) showed the SRY region translocated to the short arm of the X chromosome.J Assoc Clin Endocrinol Diabetol Bangladesh, January 2025;4(1): 34-38